Pre-aging of the Olfactory Bulb in Major Depression With High Comorbidity of Mental Disorders - Rottstaedt, Fabian; Weidner, Kerstin; Hummel, Thomas; Croy, Ilona (Frontiers in Aging Neuroscience, 2018)
Recent studies suggest that accelerated aging of the brain is a neuroanatomical signature of the state of mental diseases. In major depression, this pre-aging effect is negatively associated with the duration since the first onset of the disease. The Olfactory Bulb (OB) shrinks with age in healthy subjects and patients with mental diseases show reduced OB volumes, especially those with major depression. It is unclear whether this OB reduction in mental diseases resembles a pre-aging process and whether it is associated to the duration since the onset of the mental disease. To this aim, we investigated OB volume in 73 patients (mean-age 40.4 years, SD=12.1 years, 57 women) with major depression and mixed comorbid mental diseases (diagnoses ranged from 1 to 6, median: 3) and 51 healthy controls (mean-age 39.2 years, SD=13.0 years, 26 women) matched for age and sex. Patient’s first onset of disease ranged from 15 to 53 years (mean 24.2 years). All participants underwent structural MR imaging with a spin-echo T2-wheighted sequence covering the anterior and middle segments of the skull base. All results were corrected for total intracranial volume and sex. Individual OB volume was calculated by planimetric manual contouring and the pronounced diameter change in transition from bulb to tract was used as the distal demarcation of the OB. Inter-rater correlation between two independent persons analyzing the data was high (IRC=.81, p<.005). An age-dependent decline of the OB volume was confirmed in healthy controls (r=-.34, p<.05). However, this pattern was altered in patients where the OB volume was not related to age, but to the duration since the onset of the mental disease (r=-.25, p<.05). This association remained stable when controlling for age. Additionally, analyses of age sub-groups revealed that the association between duration since the onset of the mental disease and OB volume was mainly driven by the group aged 50 years and above (r=-.68; p<.01). We conclude that there are time windows where the OB volume is susceptible for the effects of a mental disease, e. g. depression. These effects result in cumulative pre-aging in the OB in older patients with mental diseases.